Territorialidad urbana y seguridad. Una agenda en materia de capital social para el programa Pilares de la Ciudad de México (2021)
Based on a socio-territorial analysis, guided by the concept of social capital, this article describes the insecurity conditions in which four facilities of Mexico City´s Points of Innovation, Liberty, Art, Education and Knowledge (Pilares, for its acronym in Spanish) program operate. In accordance with this purpose, we begin with the characterization of the Pilares program; later we present the conceptual section focused on social capital, a notion associated with security and urban space, which serves as a guide to the challenges and opportunities of each scenario of the program studied. Subsequently, we discuss in depth the socio-territorial security analysis of the four neighborhoods in which the selected Pilares are located, in the Cuauhtémoc and Iztapalapa districts. We conclude with the challenges and opportunities to generate social capital, which is aimed at containing violence in these Pilares.